2015
DOI: 10.1007/s11356-015-5641-x
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the dynamics of DDT in a remote tropical floodplain: indications of post-ban use?

Abstract: Significant knowledge gaps exist regarding the fate and transport of persistent organic pollutants like dichlorodiphenyltrichloroethane (DDT) in tropical environments. In Brazil, indoor residual spraying with DDT to combat malaria and leishmaniasis began in the 1950s and was banned in 1998. Nonetheless, high concentrations of DDT and its metabolites were recently detected in human breast milk in the community of Lake Puruzinho in the Brazilian Amazon. In this work, we couple analysis of soils and sediments fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 78 publications
0
6
0
1
Order By: Relevance
“…Only three out of 24 identified models were developed, calibrated and validated in tropical or sub-tropical areas: the Dynamic Multimedia Environmental Fate Model [22] was developed for the tropical floodplains of Brazil, the Chemical Fate Model [18] was developed for a tropical river catchment in Australia and the Pesticides RIsks in the tropics to Man, Environment and Trade Pesticide model (PRIMET) [34] was developed in Southeast Asia and later adapted to Ethiopia (PRIMET-Ethiopia) [79]. Some models were developed elsewhere, but applied in tropical and sub-tropical areas.…”
Section: Resultsmentioning
confidence: 99%
“…Only three out of 24 identified models were developed, calibrated and validated in tropical or sub-tropical areas: the Dynamic Multimedia Environmental Fate Model [22] was developed for the tropical floodplains of Brazil, the Chemical Fate Model [18] was developed for a tropical river catchment in Australia and the Pesticides RIsks in the tropics to Man, Environment and Trade Pesticide model (PRIMET) [34] was developed in Southeast Asia and later adapted to Ethiopia (PRIMET-Ethiopia) [79]. Some models were developed elsewhere, but applied in tropical and sub-tropical areas.…”
Section: Resultsmentioning
confidence: 99%
“…Boxall et al (2009) identified the need to generate flood emersion models in the context of chemical exposure pathways for agricultural systems. Since their review, a handful of studies have developed modelling frameworks that investigate the impact of flood dynamics on chemical fate and transport (e.g., Mendez et al, 2016;Camenzuli et al, 2012). Camenzuli et al (2012), for example, developed a model to simulate flooding within an Australian river basin and the impact of this on the mobilization of diuron.…”
Section: Capturing the Impact Of Changes In Extreme Weather Events An...mentioning
confidence: 99%
“…Road crossings block streams and alter instream habitat, connectivity, and biological assemblages (Leal et al, 2016; Leitão et al, 2018). Control of insect vectors of diseases has employed widespread use of DDT (now prohibited, although persistent) and other pesticides that contaminate aquatic ecosystems and their biota (Mendez et al, 2016).…”
Section: Environmental Issues In Floodplain Lakes and Their Implications For Aquatic Conservationmentioning
confidence: 99%